Serbian lymphoma study group: Demografic characteristics of 257 patients with follicular lymphoma - Simonović Olivera; Mačukanović-Golubović Lana; Anđelić Boško; Antić Darko; Mihaljević Biljana (Vojnosanitetski Pregled)
Background/Aim. Follicular lymphoma (FL) is a B-cell tumor usually with indolent clinical course, yet in some cases the course of the disease can be very aggressive. The aim of the re-search was to determine distribution of patients into prognostic groups based on the International Prognostic Index (IPI) and Folicular Lymphoma International Prognostic Index (FLIPI) criteria, as well as to determine the importance of classifying patients into the prognostic groups, since this could potentially have the influence on selection of the treatment modality. Methods. The retrospective study was performed on 257 patients with follicular lymphoma diagnosed between January 2000 and April 2011. Results. Based on the IPI score, 153 (59.53%) patients had low risk, 57 (22.18%) low intermediate risk, 15 (5.84%) high intermediate risk, 9 (3.50%) high risk, whereas the classification of 23 patients diagnosed with FL remained with unknown risk according to the IPI. Based on the FLIPI prognostic index, 113 (43.97%) patients had low risk, 70 (27.24%) intermediate risk and 51 (19.84%) high risk, whereas the classification of 23 (8.95%) patients remained unknown. On the basis of the FLIPI 2 prognostic index, 48 (18.68%) patients had low risk, 145 (56.42%) intermediate risk and 41 (15.95%) high risk. The classification into prognostic groups for 23 (8.95%) patients remained unknown. According to the IPI, FLIPI and FLIPI 2 there were the patients that required treatment in all the risk groups. Conclusion. The FLIPI and FLIPI 2 effectively identify patients at high risk, thus helping in treatment decision for each single patient.